2016
DOI: 10.1002/cbdv.201500043
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Plants from the Genus Phlegmariurus

Abstract: Phlegmariurus is a genus of ca. 200 species in the family Huperziaceae. Up to now, six species of the Phlegmariurus genus have been chemically investigated, and 89 compounds, including Lycopodium alkaloids possessing diverse structures and serratane-type triterpenes, have been isolated. These compounds show potent bioactivities, such as acetylcholinesterase inhibitory and cytotoxic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…These conditions impose great monetary and emotional costs on patients and their caregivers. HupA is approved as the drug of choice for Alzheimer's disease (AD) treatment in China and as a dietary supplement in the United States [29,30], as intake can improve AD pathogenesis [31]. Due to its potent AChEI activity, HupA is used as a treatment for AD.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions impose great monetary and emotional costs on patients and their caregivers. HupA is approved as the drug of choice for Alzheimer's disease (AD) treatment in China and as a dietary supplement in the United States [29,30], as intake can improve AD pathogenesis [31]. Due to its potent AChEI activity, HupA is used as a treatment for AD.…”
Section: Introductionmentioning
confidence: 99%
“…The dichloromethane-methanol (1 : 1) extract of plant materials was analysed using chromatographic techniques including preparative HPLC to afforded 15 compounds, one of which is new. From the isolated compounds, two of them (1-2) are sesquiterpene acids and thirteen of them (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) are sesquiterpene lactones. Compounds 6 and 7 were found in large quantity and hence considered as marker compounds for the identification of I. confertiflora form other species of the genus.…”
Section: Discussionmentioning
confidence: 99%
“…[7] A review of literature has shown that different secondary metabolites including monoterpenes, sesquiterpenes, diterpenes, flavonoids, and glycolipids have been reported from this genus. [8] Cyclic sesquiterpenes were found to be the predominant constituents within the genus. Though several species in the genus Inula have been scientifically studied for their phytochemical constituents and pharmacological activities, reports on the phytochemical constituents of I. confertiflora are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from Huperzia serrata (Lycopodiaceae) inhibited AChE activity and ameliorated the cognitive impairment of AD mice [ 165 ]. A number of lycopodium alkaloids have been isolated and synthesized as potent AChE inhibitors [ 166 ]. Extracts from Crocus sativus (Iridaceae) exhibited moderate inhibitory activity against AChE.…”
Section: Neuroprotective Mechanisms Of Natural Products For Admentioning
confidence: 99%